2022
DOI: 10.1002/bse.3212
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing coordination strategy of circular supply chain in re‐commerce industry: A game theoretic approach

Abstract: The circular economy seeks to reduce waste by reusing, refurbishing, and recycling used products. It increases the resource value of used goods. In this study, we proposed a circular business gap exploiter model in which a re-commerce company exploits residual value in product systems utilization. A game-theoretic approach is used to investigate the coordination problem of a two-echelon circular supply chain with e-commerce and re-commerce companies. In addition, we proposed a coordinated structure under the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Previous studies have tried to model the effect of contracts and channel coordination in CSCs (e.g. Agrawal et al, 2022), also considering the role of advanced technologies and supply chain digitalization (Chen et al, 2022).…”
Section: Circular Supply Chain Models: Collaboration Configuration An...mentioning
confidence: 99%
“…Previous studies have tried to model the effect of contracts and channel coordination in CSCs (e.g. Agrawal et al, 2022), also considering the role of advanced technologies and supply chain digitalization (Chen et al, 2022).…”
Section: Circular Supply Chain Models: Collaboration Configuration An...mentioning
confidence: 99%
“…Supply chain coordination and improved communication between different supply chain echelons can effectively overcome the challenges in achieving a CE (Bag and Rahman, 2021). Agrawal et al (2023) used a game theoretic approach to understand the coordination problem in a supply chain with two echelons. Their study revealed the efficient impact of extended product and resource value in implementing a circular business model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Retailers and manufacturers contribute to the circular economy through reusing, refurbishing and recycling returned products (Agrawal et al, 2022), which is reflected in Figure 1. To capture sustainability targets in product returns and understand its management, retail product return frameworks need to be developed and applied (Frei et al, 2020).…”
Section: Background and Theoretical Foundationsmentioning
confidence: 99%